Inclusive physical literacy model based on video modeling to facilitate movement skills and physical activity in children ADHD - Arief Darmawan; Gema Fitriady; Zihan Novita Sari; Ahadi Priyohutomo (Physical Education Departement of University PGRI Jombang, 2026)
Research Problems: Children with Attention Deficit Hyperactive Disorder are one of the developmental disorders that have low concentration, are active in moving but still do not have direction, goals and tend to be impulsive. ADHD children have limitations in the development of motor activities so that increased activity is not directed and tends to lose control. The importance of physical activity and motor skills for children with ADHD is currently experiencing quite serious problems. Methods: this study was adopted from ADDIE research and development which is divided into the stages of analyze, design, develop, implementation and evaluation. The sampling technique in this study used proportional random sampling, with subjects consisting of attention deficit hyperactivity disorder inclusion students, who are in the Malang City area, Indonesia, the subjects in the study were 30 students. A product testing questionnaire with a Likert scale was employed as the study's tool. The study's data analysis involved reducing the model's expert evaluation results, which were subsequently examined using quantitative descriptive percentage analysis. Results: of the study on a limited scale group trial showed an average gain of 84% with a very good category, while the large scale trial showed a score gain of 85% with a very good category. Conclusion: findings support the literature that suggests that physical activity-based interventions provide significant benefits in inclusive education.